CHEMICAL CONTROL OF SOUTHERN LEAF BLIGHT OF MAIZE CAUSED BY HELMINTHOSPORIUM MAYDIS - SHAH, JA; RAMZAN, U; NASEER, S; KHALID, MN; AMJAD, I; MAJEED, T; SABIR, W; SHAHEEN, MK; ALI, B; SHAHMIM, F; et al. (Biological and Clinical Sciences Research Journal, 2023)
Southern Leaf Blight of maize (SLBM) is a severe disease affecting maize crop in Pakistan. This disease causes considerable losses in maize crop every year. To avoid this loss, a study was conducted to check the efficacy of four fungicides and one control, tested against maize variety Malka-2016. The experiment was conducted at Plant Pathology AARI Research area, Faisalabad, during 2021-22. The result showed that Propiconazole (Tilt 25% WP) was found to be the most effective fungicide to control the leaf Blight of maize followed by Dithane M-45 (Mancozeb 80%WP) and Kavach (Chlorothalonil 75%WP). The Blitox-50 (Copper oxychloride 50%WP) was the least effective against the disease. The Propiconazole (Tilt 25% WP) control the disease 80 % over the check. Similarly, Dithane M-45 (Mancozeb 80 %) controls the disease 70.83 % and Chlorothalonil by 59 %. The least effective fungicide was Blitox-50 (Copper oxychloride 50 %) which control the disease 42.5% over the check.